Employing information technology methods to strengthen our fight against COVID-19 pandemic - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Wolters Kluwer Medknow Publications, 2020)
The coronavirus disease-2019 (COVID-19) pandemic has affected almost every person across the world and it is high time that we reach to each and every one of them with reliable information at the earliest to minimize the risk of acquisition as well as transmission of the infection. In these testing times, there is an immense need to utilize the communication technology in the various activities of the disease mitigation, treatment and advocacy, communication and social mobilization. It is important to acknowledge that this is the first pandemic in which technology and social media are simultaneously being utilized to ensure people safety. In conclusion, in the battle against the COVID-19 pandemic, information technology and social media have emerged as one of the important tools for the health sector to create not only awareness about the disease, but also it has aided in the prevention and control of the novel viral infection.